PERUBAHAN PELAYANAN KLINIK NON-BPJS SEBELUM DAN SETELAH IMPLEMENTASI BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN (Studi Kasus di Klinik Utama Rawat Inap Sumber Bahagia, Depok, Jawa Barat) - Gregorius Budi Rooseno Putro; Hari Kusnanto (Journal of Health Service Management, 2016)
Background: The implementation of the BPJS Kesehatan as asingle payer healthcare cover back in 2014 in Indonesia starts anew era of a nationwide coverage of health insurance. Everycitizen should be a member of that program, according to thelaw. The state owned health services are the main providers ofthe services, along with the private owned hospitals and clinics,as long as they can fulfill the requirements given by thegovernment. But some small clinics are not eligible to met thecriteria of the BPJS Kesehatan, resulting in the inability to be theprovider. This can lead to the decrease of revenues of thoseclinics, and can cause bankruptcy. Objective: The main objective of this research is to find fewalternative strategies that can be applied by the non-BPJSclinics so they can still gain a significant portion of the healthservice industry business and even increase their revenues byapplying those strategies. Methods: This research is a case study conducted in a cliniccalled KURI Sumber Bahagia in the city of Depok, West Java,with using both quantitative data of patient visitation, that wasanalysed using a linear regression technique to determine thesignification effect of BPJS Kesehatan, as well as qualitativeinformation gathering by means of interviewing the stakeholdersin that clinic. The interview data would help theresearcher to explain the phenomena found by the statisticsmeasurements. Results: The statistic results of this research showed asignificant decrease (p<0,05) in patient visitation after theimplementation of BPJS Kesehatan back in 2014, especially intypes of services such as manual labour, sectio caeserea labor,infant immunisation in general, and birth control shots. Incontrast, there are several services that showed an increaseusage (p<0,05) even after BPJS Kesehatan, such as IUDsservices, Hepatitis A shots, and Cervical Cancer shots. Basedon the interview conducted afterwards, researcher found onmost health services, patients tend choose BPJS than privateclinics of the same services because it is cost efficient, but onsome services they were willing to pay out of pocket in privateclinics because the quality of services or the products that werenot available in BPJS Kesehatan (eg. NOVA T brand of IUD).Furthermore, the research also found the increase on serviceswhich are not available in BPJS Kesehatan (eg. Hepatitis Ashots, Cervical cancer shots). Conclusion: There are significant decreases of patientvisitation numbers in KURI Sumber Bahagia clinic since theimplementation of BPJS Kesehatan. This phenomenon isresponded by the clinic by giving a better quality services andproducts and also by providing other services in which notcovered by BPJS Kesehatan. Differentiation of services and quality services is proven effective to maintain and evenincrease patient visitation, which in the end can give a goodrevenues for the clinic.